HUBUNGAN TINGKAT STRES KERJA DENGAN KINERJA PERAWAT DI INSTALASI BEDAH SENTRAL RSUD RADEN MATTAHER JAMBI TAHUN 2023 - M. Sandita Siregar; Marinawati Ginting; Nia Nurzia; Sondang Selviana (Universitas Adiwangsa Jambi, 2024)
Work stress often occurs among workers in the health sector. Borril and Charnley (2012) in Yana (2014) stated that although all professional staff in hospitals are at risk of stress, nurses have higher levels of stress.Nurses act as important liaisons in a hospital, one example is a surgical room nurse. The duties and responsibilities of operating room nurses are not light things to bear. Performance is real behavior displayed by each person as a work achievement produced by employees in accordance with their role in the company.The performance of nurses in this room in 2015 showed that 51.8% of nurses still had sufficient performance. Work stress is one of the things that influences employee performance. The aim of this research was to determine the relationship between work stress levels and the performance of surgical room nurses at RSU Raden Mattaher Jambi.This research design uses descriptive observational with a cross sectional approach. The population was all 65 operating room nurses. The sampling method used is total sampling. The independent variable is the level of work stress and the dependent variable is the nurse's performance. Data collection uses questionnaire sheets and statistical tests. The results of the chi-square test obtained a p-value of 0.018<0.05, which means that Ho was rejected, so it was concluded that there was a relationship between work stress and the performance of surgical room nurses at the Central Surgery installation at the Raden Mattaher General Hospital, Jambi in 2023.The high level of work stress of nurses is related to nurses' performance being at an adequate level. The lower the level of work stress, the better the nurse's performance will be. To reduce work stress levels, nurses need to carry out work stress management training so that performance becomes better.The suggestion from this research is that RSUD Raden Mattaher Jambi can make more efforts to reduce work stress in operating room nurses and in other rooms or units